2016
DOI: 10.1140/epjc/s10052-016-4303-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Cosmology of f(R, T) gravity

Abstract: Modified gravity theories have the potential of explaining the recent acceleration of the Universe without resorting to the mysterious concept of dark energy. In particular, it has been pointed out that matter-geometry coupling may be responsible for the recent cosmological dynamics of the Universe, and matter itself may play a more fundamental role in the description of the gravitational processes that usually assumed. In the present paper we study the quantum cosmology of the f (R, T ) theory of gravity, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…The thickness of the resulting film is solely controlled by the thickness of the bulk precursor film. Xu et al [152] followed this work and developed an approach to increase the grain size with a flash evaporation process by varying the pressure and the precursor composition ratios. The resulting morphology change can be seen in Figure 14b.…”
Section: Flash Evaporation and Close Space Sublimation (Css)mentioning
confidence: 99%
See 2 more Smart Citations
“…The thickness of the resulting film is solely controlled by the thickness of the bulk precursor film. Xu et al [152] followed this work and developed an approach to increase the grain size with a flash evaporation process by varying the pressure and the precursor composition ratios. The resulting morphology change can be seen in Figure 14b.…”
Section: Flash Evaporation and Close Space Sublimation (Css)mentioning
confidence: 99%
“…b) SEM images of morphology changes from flash evaporation with different processing parameters. [152] c) Illustration of close space sublimation process. d) Photograph of perovskite film deposited via close space sublimation.…”
Section: Vapor-assisted Solution Process and Ion Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…(9) it follows that the matter energy-momentum tensor is not conserved, and its divergence is given by [52] (for the computational details see Appendix B), …”
Section: The Metric Formalismmentioning
confidence: 99%
“…Compared to f (R) theory, the field equations are second order instead of fourth one, which is an important advantage of f (T ) theory. As a further extension, and an analogy to that of f (R) theories [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], non-minimal torsion-matter coupling f (T ) gravity has been proposed and studied [30]. In the previous research [31], using the observation data of type Ia supernovae (SNeIa), cosmic microwave background (CMB), and baryon acoustic oscillations (BAO), we established two concrete f (T ) models with non-minimal torsion-matter coupling extension, and we found that they are successful in describing the observation of the Universe and its large-scale structure and evolution.…”
Section: Introductionmentioning
confidence: 99%